Does oil rent increase happiness? A partial efficiency analysis of selected African countries - Seun Sylvester Opaleye; Chijioke Esogwa Nwachukwu (Trends Economics and Management, 2019)
Purpose of the article: To investigate and ascertain the impact of oil rent on happiness in selected African countries. Methodology/methods: This study employed the trend analysis to graphically illustrate some major data. It also employed the fixed effect to analyse the model and the partial efficiency analysis to rank the countries studied in terms of their efficiency in the use of oil rent to produce happiness. Scientific aim: This study examines the relationship between oil rent, the oil price, the GDP growth, the mineral rent and happiness. Findings: The results show that oil rent does not significantly increase happiness in the countries studied with Cameroun being the happiest country in the panel. Oil prices however significantly increased happiness. The study also found that the economic growth reduces happiness. Conclusions: The study provides evidence that the economic growth alone does not lead to happiness in the country if citizens are not employed and the rate of inflation continues to spiral upward. The study thus concludes that the economic growth must be inclusive in nature through government use of rents to invest in sectors that create value additions and job opportunities for citizens. The study also recommends the setting of the social safety net, as well as ensuring that inflation is properly managed.
Keywords: M15; M21; 650; oil rent; mineral rent; inflation; unemployment; happiness